ANALISIS RISIKO PRODUKSI DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA PADA USAHATANI JAGUNG (Zea mays L.) DI KECAMATAN MEMPAWAH HULU KABUPATEN LANDAK - Kurniati, Dewi (Jurnal Social Economic of Agriculture, 2012)
Abstract This study aims to analyze the production risk of maize farming and also find effect of using maize farming input toward the production risk. The method used in this study is a survey method . The location is determined by purposive. Data obtained through interviews with 60 randomly simple maize farmers. The method used is coefficient of variation (CV) analysis and multiple linear regression analysis with heteroscedastic method. The results showed that the production risk of maize farming with land area < 1 ha higher than maize farming with land area ??1 ha. The production risk is influenced by labor , with coefficient value is -0.027 ??and probability value is 0.09 . The number of labor significantly influence the variation of maize production, so that means additional labor affect production risk of maize farming. Key words: risk, production, maize farming